Studi Laboratorium Analisis Penambahan CaCO3 pada Berbagai Temperatur terhadap Lumpur Pemboran - Gevani, Sheren; Sahrudding; Sinurat, Daniel (Jurnal Offshore: Oil, Production Facilities and Renewable Energy, 2025)
In this research, the effect of temperature on drilling mud with and without the addition of CaCO₃ was analyzed. The objectives of this study were to determine the changes in mud weight, rheology, filtrate volume, and pH under three temperature variations: 80°F, 130°F, and 180°F for original mud, 3% CaCO₃, and 5% CaCO₃ formulations. Laboratory-scale experiments were conducted. The results showed that mud weight decreased with increasing temperature in all formulations. The mud without CaCO₃ decreased from 9.32 ppg to 7.9 ppg. With 3% CaCO₃, mud weight decreased from 10 ppg to 9.13 ppg, while 5% CaCO₃ showed a reduction from 10.28 ppg to 9.83 ppg. Rheological properties including plastic viscosity (PV), yield point (YP), and gel strength (GS) decreased with temperature increases. Filtrate volume increased at higher temperatures for all mud variations. Meanwhile, pH decreased from 80°F to 130°F but remained constant afterward. Overall, the addition of CaCO₃ improved mud performance but temperature significantly influenced mud properties.